Developmental Counselling and Psychological Education - An Integrated Conceptual Framework - Van Hesteren, Frank (Canadian Journal of Counselling and Psychotherapy, 2012)
It is suggested that psychological education represents a potentially useful medium through which important developmental counselling goals might be realized in the school setting. While this concept appears to hold considerable promise for counsellors and teachers, there is at present a need to clarify the place and contribution of psychological education in the context of school related factors contributing to pupil development. Given this need for clarification, an integrated conceptual framework for psychological education is presented and discussed.